PENGARUH KOMPETENSI KEDISIPLINAN DAN KEPEMIMPINAN TRANSFORMASIONAL KEPALASEKOLAH TERHADAP KINERJA GURU PADA SD RADEN PATAH SURABAYA - Angella Ismi Oktaviani; Yanuar Fauzuddin (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze how Competence, Discipline and Transformational Leadership affect the Teacher Performance of SD Raden Patah, Surabaya. The number of samples taken was 32 teacher respondents at SD Raden Patah, Surabaya. Data collection techniques by distributing questionnaires. The analysis used is the validity test, reliability test, classical assumption test, multiple linear regression analysis and the coefficient of determination. The results of this study indicate that: (1) Competence has a positive and significant effect on the Teacher Performance of SD Raden Patah, Surabaya. (2) Discipline has a positive and significant effect on Teacher Performance at SD Raden Patah, Surabaya. (3) Transformational leadership has a positive and significant effect on teacher performance at SD Raden Patah, Surabaya. (4) Competence, Discipline and Transformational Leadership simultaneously have a positive and significant effect on the Teacher Performance of SD Raden Patah, Surabaya.